Optimizatsiya postroeniya trenirovochnykh nagruzok v protsesse podgotovki kvalifitsirovannykh plovtsov - Davydov, V. Ju.; Prytkova, E. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Load parameters of elite swimmers are presented and discussed. In the relation to the training the development of parameters as body mass, lean body mass or muscle mass are analysed (mesocycle by mesocycle).